If you do do 4 × 13 = 39 you will get it wrong.
Working it out: 4 × 13 = 52
To get 39, you need to calculate: 3 × 13 = 39.
3 x 13
13 time 3 = 39.
13 and 3. Isnt it?
39 ÷ 3 = 13
6 times 13 equals 78 3 times 26 equals 78 2 times 39 equals 78 and 1 times 78 equals 78
3 times 13 will equal 39
"cubed" is multiplied by itself 3 times ie 13 x 13 x 13 = 2197 39 is 13 + 13 + 13. Big difference!
3x13=39
3*13=39
Each of these factor pairs (multiply the numbers in parentheses) equals 1,521: (1, 1521) (3, 507) (9, 169) (13, 117) (39, 39)
1 times 39, perhaps.
13+c = -39 c = -39-13 c = -52